Faktor-Faktor Yang Mempengaruhi Corporate Social Disclosure Pada Perusahaan Manufaktur Di London Stock Exchange - Siti Markhamah; Indah Fajarini Sri Wahyuningrum (Gorontalo Accounting Journal, 2020)
The purpose of this study was to analyze the influence of firm age, leverage, profitability, liquidity, and gender on corporate social disclosure. Corporate social disclosure is measured using content analysis methods based on GRI Standards 2016. This research is based on a quantitative method using multiple linier regression analysis. The population of this study is manufacturing companies listed on London Stock Exchange in 2015-2017. The data analysis tool used is the IBM SPSS 21 program. The conclusion of this study is that leverage variable has a significant negative effect on corporate social disclosure, while firm age, profitability, liquidity, and gender variables have no significant effect on corporate social disclosure. The results showed that leverage has a negative and significant effect on corporate social disclosure. Firm age, profitability, liquidity, and gender have not a significant effect on corporate social disclosure.